Commercial Floriculture Industry in India : Status and Prospects (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The present paper discusses about the status of Hitech floriculture industry in India. The present status of commercial floriculture industry is discussed. Alongwith this, the problems and prospects of the industry is are highlighted. The floriculture industry is characterized by traditional as well as modern cut flowers. The cutflower industry is rapidly growing worldwide. While this industry is dominated by selected European countries as well as US and Japan, the production base is shifting from these countries to low cost countries like Kenya, Colombia, India and China. While much needs to be done, Indian floriculture industry has lot of potential of growth. The consumption within India is increasing with changing socio economic structure as well as effects of globalization. At the same time, India is preparing itself to take an increasing role in the world trade of floriculture, which at present is miniscule. The government has recognized the importance of this industry and hence given a special focus to this industry. The National Horticulture Mission is an endeavor of the government to promote holistic development of floriculture and with an integrated approach towards cluster development.